(R)-(+)-α-Lipoic acid protected NG108-15 cells against H2O2-induced cell death through PI3K-Akt/GSK-3β pathway and suppression of NF-κβ-cytokines - Kamarudin MNA; Mohd Raflee NA; Syed Hussein SS; Lo JY; Supriady H; Abdul Kadir H (Dove Medical Press, 2014)
Muhamad Noor Alfarizal Kamarudin, Nur Afiqah Mohd Raflee, Sharifah Salwa Syed Hussein, Jia Ye Lo, Hadi Supriady, Habsah Abdul KadirInstitute of Biological Sciences, Faculty of Science, University of Malaya, Kuala Lumpur, MalaysiaAbstract: Alpha-lipoic acid, a potent antioxidant with multifarious pharmacological benefits has been reported to be neuroprotective in several neuronal models and used to treat neurological disorders such as Alzheimer’s disease. Nonetheless, conclusive mechanisms of alpha-lipoic acid for its protective effects particularly in NG108-15 cells have never been investigated. In this study, the intricate neuroprotective molecular mechanisms by (R)-(+)-alpha-lipoic acid (R-LA) against H2O2-induced cell death in an in vitro model of neurodegeneration were elucidated. Pretreatment with R-LA (2 hours) significantly increased NG108-15 cell viability as compared to H2O2-treated cells and mitigated the induction of apoptosis as evidenced by Hoechst 33342/propidium iodide staining. R-LA (12.5–50 µM) aggrandized the reduced glutathione over glutathione disulfide ratio followed by a reduction in the intracellular reactive oxygen species level and an increase in mitochondrial membrane potential following H2O2 exposure. Moreover, pretreatment with R-LA stimulated the activation of PI3K-Akt through mTORC1 and mTORC2 components (mTOR, rictor and raptor) and production of antiinflammatory cytokine, IL-10 which led to the inactivation of glycogen synthase kinase-3β (GSK-3β) and reduction of both Bax/Bcl2 and Bax/Bcl-xL ratios, accompanied by inhibition of the cleaved caspase-3. Additionally, this observation was preceded by the suppression of NF-κβ p65 translocation and production of proinflammatory cytokines (IL-6 and TNF-α). The current findings accentuate new mechanistic insight of R-LA against apoptogenic and brain inflammatory factors in a neuronal model. These results further advocate the therapeutic potential of R-LA for the treatment of neurodegenerative diseases.Keywords: alpha-lipoic acid (LA), cytokines, GSK-3β, neuroegenerative diseases, NF-κβ, PI3K-Akt